The Role of Flight Instructors as Catalysts of Safety Management System in Aviation Academies: A Systematic Literature Review - Yasyfa' Kawakibi; Dimas Hari Cahyo; Hendra Sudarso (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – The objective of this article is to undertake a comprehensive literature analysis of the strategic importance of flight instructors as implementers of the Safety Management System (SMS) in Approved Training Organisations (ATOs). This review synthesizes the research to understand how instructors transform formal safety principles into everyday operational activities and presents a new conceptual framework of meso-level safety leadership for aviation schools.Methods – A qualitative topic synthesis was conducted following the PRISMA 2020 procedure. The authors collected metadata of the papers in the Google Scholar database from 2013 to 2025 with the Publish or Perish software. Twelve core peer-reviewed papers were selected for final analysis under tight inclusion and exclusion criteria and quality grading procedures to limit the subjectivity of single-researcher selection.Findings – Instructors are essential bridges in the meso-layer, transferring explicit SMS rules into everyday actions. These instructors create psychologically safe environments during non-punitive debriefs, fostering an organic safety culture. However, the academic “pressure to fly” and high staff turnover severely limit this catalytic impact. We have developed the ‘Meso-Catalytic Safety Leadership Framework’ to show that generative safety is really the intersection of great meso-leadership and a psychologically secure climate.Research Implications – The results have practical implications for ATO administrators to restructure Flight Instructor standardization programs with the integration of emotional intelligence and scenario-based safety leadership training. The limitation of the technique is that the current literature is cross-sectional. For future research methodology for an exploratory study, we would recommend longitudinal designs and the ability to apply artificial intelligence reporting systems to offset the loss of institutional memory.